1996
DOI: 10.1007/bf00171067
|View full text |Cite
|
Sign up to set email alerts
|

Participation of nitric oxide in the relaxation of the rat gastric corpus

Abstract: Nitric oxide is an important mediator of the relaxation in the rat gastric fundus. The present study investigates the role of NO in the rat gastric corpus in vitro, since the corpus differs from the fundus with regard to its physiological function and its spontaneous motor behaviour. In the presence of guanethidine electrically induced relaxations of circular, mucosa-free corpus strips precontracted with bethanechol were concentration-dependently reduced by the NO-synthase inhibitors L-NG-nitro-arginine (L-NNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…However, in the presence of L-NAME, ghrelin did not produce significant change of the S2/ S1 ratio (control = 0.87, ghrelin = 0.96). Since nitric oxide has been demonstrated to decrease acetylcholine release in the rat stomach, 38 the present results suggest that ghrelin activates nitrergic neurons and that the released nitric oxide decreases [ 3 H]-efflux. The ghrelin receptor has been demonstrated to be expressed on nitrergic neurons in the rat stomach, and ghrelininduced nitric oxide release was confirmed by using microdialysis techniques.…”
Section: Discussionsupporting
confidence: 58%
“…However, in the presence of L-NAME, ghrelin did not produce significant change of the S2/ S1 ratio (control = 0.87, ghrelin = 0.96). Since nitric oxide has been demonstrated to decrease acetylcholine release in the rat stomach, 38 the present results suggest that ghrelin activates nitrergic neurons and that the released nitric oxide decreases [ 3 H]-efflux. The ghrelin receptor has been demonstrated to be expressed on nitrergic neurons in the rat stomach, and ghrelininduced nitric oxide release was confirmed by using microdialysis techniques.…”
Section: Discussionsupporting
confidence: 58%
“…Although L-NNA itself had no effect on NANC relaxations in the guinea pig taenia coli, the combination of L-NNA and apamin significantly inhibited NANC relaxations compared with the inhibitory effects of apamin alone (38). Holzer-Petsche and Moser (16) demonstrated that L-NNA had no effect on NANC relaxation of the rat gastric corpus, but when combined with apamin, L-NNA significantly inhibited NANC relaxations. We propose that a complex interaction involving a prejunctional mechanism may exist between ATP and NO release.…”
Section: Discussionmentioning
confidence: 98%
“…The lack of spontaneous motor activity in the fundal strips reflects the functional role of this gastric region and implies that activation of muscle contractions in the fundus is dependent on external control, neural, and/or hormonal [39,40]. Contractile responses can be easily obtained in fundal gastric strips by means of EFS.…”
Section: Discussionmentioning
confidence: 99%